Reshaping agriculture for nutrition and health - Fan, Shenggen; Pandya-Lorch, Rajul (International Food Policy Research Institute, 2012)
The fundamental purpose of agriculture is not just to produce food and raw materials, but to grow healthy, well-nourished people. One of the sector’s most important tasks then is to provide food of sufficient quantity and quality to feed and nourish the world’s population sustainably so that all people can lead healthy, productive lives. Achieving this goal will require closer collaboration across the sectors of agriculture, nutrition, and health, which have long operated in separate spheres with little recognition of how their actions affect each other. It is time for agriculture, nutrition, and health to join forces in pursuit of the common goal of improving human well-being.